Analisis Hukum Terhadap Tindak Pidana Pertambangan Pasir Yang Dilakukan Secara Ilegal : Studi Putusan Pengadilan - Polin Pangaribuan; Muhammad Hamdan; Edi Yunara; Marlina Marlina (Universitas Sumatera Utara, 2019)
Abstract. In Law No. 9 of 2009 on Mining it is explained that in Mining there are several articles containing the provisions of criminal sanctions for those who violate them. Looking at the titles and topics of the research, the discussion of criminal provisions only focuses on illegal sand mining practices mentioned in Article 158 and Article 161 of Law No. 4 of 2009 on Mining. The subject matter of the study is Legal Provision on illegal sand mining. How the judge judges judgment of illegal sand mining perpetrators (decision number 132 / Pid.Sus / 2015 / PN Lmj), (Decision number: 123 / Pid.Sus / 2015 / PN Pbg), (Verdict number: 92 /Pid.Sus/2012/PN.Kdi). Types of research normative legal research, the nature of the research is descriptive, evaluative, prescriptive, Legal data source data obtained from library research, assisted with the Judgment Study Court, Legal provisions on unlicensed sand mining are provided in Article 158 and Article 161, it is explained that in Mining there are several articles containing the provisions of criminal sanctions for those violating them. Judge's consideration in deciding illegal sand mining perpetrators (decision number 132 / Pid.Sus / 2015 / PN Lmj), (Decision number: 123 / Pid.Sus / 2015 / PN Pbg), (Decision number: 92 / Pid.Sus / 2012 / PN.Kdi) is based on legal facts, testimony of witnesses, statements of defendants, evidence, matters that lighten and incriminate the defendant. Keywords: crime, sand mining, illegally